High-fat diet-induced dysregulation of ovarian gene expression is restored with chronic omega-3 fatty acid supplementation. (1st January 2020) - Hohos, Natalie M.; Elliott, Emily M.; Cho, Kirstin J.; Lin, Ivy S.; Rudolph, Michael C.; Skaznik-Wikiel, Malgorzata E.
Abstract: Chronic high-fat diet (HFD) consumption causes ovarian dysfunction in rodents. Acute dietary treatment with docosahexaenoic acid (DHA) increases oocyte quality and ovarian reserve at advanced reproductive age. We hypothesized that DHA supplementation after HFD exposure reverses HFD-induced ovarian defects. We conducted a dietary intervention with reversal to chow, DHA-supplemented chow, or DHA-supplemented HFD after HFD consumption. After 10 weeks, HFD-fed mice had impaired estrous cyclicity, decreased primordial follicles, and altered ovarian expression of 24 genes compared to chow controls. Diet reversal to either chow or chow + DHA restored estrous cyclicity, however only chow + DHA appeared to mitigated the impact of HFD on ovarian reserve. All dietary interventions restored HFD-dysregulated gene expression to chow levels. We found no association between follicular fluid DHA levels and ovarian reserve. In conclusion our data suggest some benefit of DHA supplementation after HFD, particularly in regards to ovarian gene expression, however complete restoration of ovarian function was not achieved. Highlights: Diet reversal with DHA supplementation after HFD restores ovarian gene expression. DHA supplemented to chow after HFD appears to prevent ovarian reserve decline. DHA has no additional benefit to reversal to chow on improving estrous cyclicity.